AFRICAN SWINE FEVER, STREPTOCOCCOSIS AND COCCIDIOSIS IN PIG AT PUHU VILLAGE, PAYANGAN, GIANYAR - Yeyen Agustianingsi; I Nyoman Mantik Astawa; Hapsari Mahatmi; Ida Bagus Oka Winaya; I Putu Cahyadi Putra (Buletin Veteriner Udayana, 2024)
This case study aims to discuss the anatomical pathology, histopathology, and laboratory examination results to obtain a definitive diagnosis of the disease affecting 4 month old pigs from Puhu Village, Gianyar. Data collection in the form of indications, anamnesis, epidemiological and laboratory examinations for further descriptive qualitative analysis. Clinical signs of pig include anorexia, weakness, diarrhea, fever (39.7oC), multifocal cyanosis of skin, severe neurological symptoms. Epidemiological data shows morbidity reaching 100%, mortality 78.94%, and case fatality rate 78.94%. An anatomical pathology examination was carried out through necropsy procedure and found hydropericardium, hemorrhage in the heart, brain, intestines, stomach, lungs, liver, kidneys had pthechie, while spleen changed color to dark and swollen, organ samples were collected for histopathology examination. Histopathological examination begins with histological preparations using Hematoxylin-Eosin (HE) staining. Examination were carried out by looking at the changes descriptively using binocular light microscope with 100x, 400x magnification. Histopathological examination showed that the brain (hemorrhagic meningitis), lungs (hemorrhagic interstitial pneumonia), heart (myocardial edematous), spleen (hemorrhagic spleen) and small intestine (necrotizing enteritis), large intestine (hemorrhagic et necrotizing colitis). In histology preparations, inflammation was found and dominated by lymphocyte cells and a few neutrophil cells. In bacteriological examination, Samples were isolated using Nutrient Agar, Blood Agar media. Bacterial identification then carried out using the Gram stain test, catalase test, Triple Sugar Iron Agar, Sulfide Indole Motility, Methyl Red Voges Proskauer, Simmon Citrate Agar, glucose test. Bacteriological examination confirmed the presence of Streptococcus suis bacterial infection in the brain, lungs, spleen. Parasitological examination of feces was carried out using native, floating and sedimentation methods, Eimeria spp. oocysts were found and calculated using quantitative methods with McMaster technique as 30,200 oocysts/gram. Based on all data and laboratory examination results, it was concluded that the pig was infected with African swine fever, Streptococcus suis and Eimeria spp. In pig farming management, strict biosecurity and sanitation must be implemented to minimize the risk of contamination by disease agents.